Clinical Trials in Pediatric Autosomal Dominant Polycystic Kidney Disease - Cadnapaphornchai, Melissa A. (Frontiers in Pediatrics, 2017)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease and is associated with concerning long-term implications for kidney function and cardiovascular health. Early intervention is needed in order to mitigate these long-term complications. Herein we review important findings from recent clinical trials in ADPKD and their relevance to affected children and young adults and consider future directions for intervention. Recent clinical trials support aggressive control of blood pressure with blockade of the renin-angiotensin-aldosterone system as well as potential benefit of pravastatin therapy in children and young adults with ADPKD. There are several other candidate therapies, some of which have shown benefit in adult ADPKD, which require further investigation in affected children.